Asas Legalitas, Persamaan dan Pembuktian dalam Hukum Pidana Islam - Al-Nafiz; Muhammad Riyas Rasyid; Muhammad Hegel Muthohari (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2024)
This research is personal research and quotes a lot from relevant legal journals regarding the meaning of the principle of legality within the scope of Indonesian criminal law or Indonesian criminal law. The principle of legality in Indonesian Criminal Law aims to protect humans from the arbitrariness of those in power, while in Islamic criminal law the principle of legality aims to glorify humans by preserving offspring, property, reason, soul and religion. Basically, the meaning of the principle of legality in Indonesian criminal law and Islamic criminal law is not much different. However, in Islamic criminal law there is no prohibition on using analogies, whereas in Indonesian criminal law the use of analogies is not permitted.